Analysis of Sustainable Ecotourism Development Strategy: Islamic Economic Review: Case Study Deli Serdang Regency - Taqiya Zahrowaini; Reni Ria Armayani Hasibuan; Nur Ahmadi Bi Rahmani (SENTRALISASI, 2026)
This study aims to formulate a sustainable ecotourism development strategy model in Deli Serdang Regency that is integrated with Islamic Economic principles. The gap arises because the dominant conventional strategy in Deli Serdang fails to address sustainability issues, despite its vast natural potential and the increasing regional halal tourism trend. Using a qualitative descriptive approach with a SWOT analysis framework, and reviewed through Islamic economics from the perspective of Maqasid Syariah, this study analyzes the condition of ecotourism in Sikabung-Kabung, Paloh Naga, and Pematang Johar. The results of the IFAS analysis (1.33) and EFAS (1.05) place the destinations in Quadrant I (Aggressive/Growth Strategy). Resulting in a StrategyEco-Socio Tourism Based on local communities that integrate Islamic ethical service standards and education-based environmental conservation, integrated within an Islamic economic framework that balances aspects of sustainable economic benefits, environmental protection, and improving the quality of life of the community with the local foundation of maqasid sharia.while addressing infrastructure and human resource challenges, to create competitive and sustainable ecotourism.